2019
DOI: 10.1111/ajgw.12385
|View full text |Cite
|
Sign up to set email alerts
|

Validation of micrografting to identify incompatible interactions of rootstocks with virus‐infected scions of Cabernet Franc

Abstract: Background and Aims Grafted grapevines are a key component of modern viticulture. Grafting provides not only resistance to soil‐borne pests, but can also improve adaptability to the environment and can improve fruit yield and quality. Graft incompatibility induced by grapevine viruses causes damage to vineyards worldwide. The aim of the present study was to create a rapid and reliable means of evaluating graft incompatibility resulting from grafting virus‐infected scions onto healthy grape rootstocks. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 25 publications
(28 reference statements)
2
13
0
Order By: Relevance
“…A previous micrografting study with GLRaV-1 and GVA found that 'George' and 'AXR1' were less susceptible to infection by GLRaV-1 and GVA than 'Freedom' and '101-14' when used as rootstocks, suggesting that the reduced susceptibility may be a result of their Vitis. rupestris parentage [49]. Our results showed 'Hunan-1' had reduced susceptibility to GLRaV-3.…”
Section: Discussionmentioning
confidence: 55%
“…A previous micrografting study with GLRaV-1 and GVA found that 'George' and 'AXR1' were less susceptible to infection by GLRaV-1 and GVA than 'Freedom' and '101-14' when used as rootstocks, suggesting that the reduced susceptibility may be a result of their Vitis. rupestris parentage [49]. Our results showed 'Hunan-1' had reduced susceptibility to GLRaV-3.…”
Section: Discussionmentioning
confidence: 55%
“…Following the advent of in vitro plant tissue culturing in the early 1900s [7], a grafting system using tissue culture (micrografting) was first demonstrated by Doorenbos [8] in ivy and then Holmes [9] in chrysanthemum in the 1950s, and was later developed and standardized for virus eradication from citrus species by Murashige et al [10] and Navarro et al [11]. To date, in vitro micrografting (IVM) has been widely applied (1) in pathogen management to facilitate the eradication, indexing and transmission of pathogens, as well as the assessments of graft incompatibility induced by pathogen infection [11][12][13][14][15]; (2) to facilitate in vitro rooting [16][17][18][19], to invigorate regenerating plant tissue cultures during micropropagation [19][20][21][22], and for the rapid assessment of graft compatibility [23][24][25][26]; and (3) in studies focusing on the molecular mechanism of graft compatibility, as well as the exchange and trafficking of macromolecules between scions and rootstocks [27][28][29][30].…”
Section: Overall Developments and Characters Of Micrograftingmentioning
confidence: 99%
“…Several devices have been used to enable fast and effective union between the rootstock and scion, such as the elastic electric-wire tube [44], aluminum foil [66,76], Parafilm ® strip [42], silicon tube [13,79,80], paper bridge [59], silicone chip [30], plastic clamps [50] or alginate gel beads [44,75,81]. These grafting devices are used to support the graft and hold the scion and rootstock together during graft healing, particularly for the top-slit and top-wedge methods.…”
Section: Culture Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several in vitro biological methods have been described for indexing of GLRaV‐3 (Tanne et al 1996, Pathirana and McKenzie 2005a,b, Constable et al 2013, Cui et al 2015, 2017, 2019, Hao et al 2017). Compared with field studies (Cirami et al 1988, Walter et al 1990, Pathirana and McKenzie 2005a, Constable et al 2013), in vitro culture can avoid the interference of environmental factors, such as temperature, light and nutrition, and other pathogens, thus ensuring reliability of the results, in addition to its time efficiency (Tanne et al 1993, 1996, Pathirana and McKenzie 2005b, Cui et al 2015, 2016, 2017, 2019, Hao et al 2017). Grapevine plants infected with GLRD express symptoms earlier, and the symptoms are intensified in vineyards under drought stress in the autumn (Tanne et al 1996, Maree et al 2013).…”
Section: Introductionmentioning
confidence: 99%